2013
DOI: 10.4184/asj.2013.7.4.322
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Disc Degenerative Disease: Disc Degeneration Symptoms and Magnetic Resonance Image Findings

Abstract: Study DesignCross sectional and observational.PurposeTo evaluate the different aspects of lumbar disc degenerative disc disease and relate them with magnetic resonance image (MRI) findings and symptoms.Overview of LiteratureLumbar disc degenerative disease has now been proven as the most common cause of low back pain throughout the world. It may present as disc herniation, lumbar spinal stenosis, facet joint arthropathy or any combination. Presenting symptoms of lumbar disc degeneration are lower back pain and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
58
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(88 citation statements)
references
References 33 publications
9
58
0
4
Order By: Relevance
“…The cause of facet hypertrophy is increased mechanical stress due to change in posture and center of gravity. Ligamentum flavum hypertrophy is mostly seen at lower spinal level predominantly at L4/L5 and L5/S1 which was similar to the study conducted by S. Saleem, Hafeez M. Aslam et al 30 Only 2 cases of spondylolisthesis were found in our study both were involving L4/L5 level. Spondylolisthesis had been reported frequently in the patients of lumbar canal stenosis in comparison to patients of disc herniation, reflecting the fact that during stenosis, laxity of capsules and spinal ligaments may result in spondylolisthesis.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The cause of facet hypertrophy is increased mechanical stress due to change in posture and center of gravity. Ligamentum flavum hypertrophy is mostly seen at lower spinal level predominantly at L4/L5 and L5/S1 which was similar to the study conducted by S. Saleem, Hafeez M. Aslam et al 30 Only 2 cases of spondylolisthesis were found in our study both were involving L4/L5 level. Spondylolisthesis had been reported frequently in the patients of lumbar canal stenosis in comparison to patients of disc herniation, reflecting the fact that during stenosis, laxity of capsules and spinal ligaments may result in spondylolisthesis.…”
Section: Discussionsupporting
confidence: 77%
“…30 Patients of LBP diagnosed with herniated disc in MRI and those were treated surgically have better short-term outcomes in comparison to patients who treated with conservative therapy. 31 So if surgery is performed earlier after the diagnosis, prognosis will be better.…”
Section: Discussionmentioning
confidence: 99%
“…Patients of 51-70 year age group were more commonly affected; this finding is supported by studies done by Saleem et al [17] and Rai et al [14]. Modic end plate changes were seen in 21% of the present study population.…”
Section: Spectrum and Prevalence Of Degenerative Changes Seen On Mrisupporting
confidence: 81%
“…It was mostly seen at lower spinal levels (predominantly at L4/L5 and L5/S1), similar to study conducted by Saleem et al [17]. In the study done by PY Yong et al [16]14.0% manifested LFH.Vertebral compression was seen in 5.7% of the study population with anterior wedge collapse accounting for majority (90%) of cases.…”
Section: Spectrum and Prevalence Of Degenerative Changes Seen On Mrisupporting
confidence: 74%
“…In the industrialized countries, LBP is very common and lumbar disk degenerative disease is one of the main causes of LBP all over the world [2]. LBP may occur due to degenerative changes, Stenosis of spinal cord, neoplasm, injury, infection, and arthritic effects [3].…”
Section: Introductionmentioning
confidence: 99%